THE INFLUENCE OF STUNTING PREVENTION CARDS ON IMPROVING THE KNOWLEDGE OF ADOLESCENT GIRLS - Mulia Sakti, Putri; admasari, Yuli; Suryani, Lili; Sarliana, Sarliana; Hadina, Hadina; Linda, Linda (Indonesian Midwifery and Health Sciences Journal, 2025)
Stunting is one of the health issues. Prevention efforts for stunting include interventions targeted at various life stages, such as adolescence and preconception. The purpose of this study was to examine the influence of stunting prevention cards in enhancing the knowledge of adolescent girls to prevent stunting. Method: This study employed a Pre-Experimental Design with a One Group Pretest–Posttest Design, involving a sample size of 50 respondents. Data were collected using a knowledge questionnaire consisting of 10 items, each with 4 multiple-choice answer categories, with a maximum score of 100 and a minimum score of 10. The questionnaire was distributed to all respondents before the game, and the time for questionnaire completion was 20–25 minutes (pre-test). Subsequently, respondents were given 10 minutes to read the explanations of categories found on the stunting prevention cards. Afterward, a game lasting 1 hour was conducted, followed by a question and answer session lasting 25–30 minutes. Finally, respondents were given a 30-minute break before being provided with the same questionnaire again, with a questionnaire completion time of 25–30 minutes (post-test). Data were processed and analyzed univariately and bivariate using the T-test. The research results were then presented in tables and narrative form. Result: The statistical test yielded a p-value of 0.000 or p < 0.05. This indicates that the stunting prevention cards significantly influenced the increase in the knowledge level of adolescent girls. Conclusion: The higher the level of knowledge among adolescents, the better they are at preventing stunting.